The Influence of Motivation, Discipline and Self-Confidence on Student Academic Achievement in Management Study Program, Institut Manajemen Wiyata Indonesia - Zeffanya Raphael Wijaya; Sandi Sandi (Institut Manajemen Wiyata Indonesia, 2020)
The purpose of this study is to find out the influence of motivation, discipline and confidence on academic achievement. The research method used is quantitative research method with type of kausal relationship research or reciprocal relationship. The research samples taken were all students of Management Study Program of Institut Manajemen Wiyata Indonesia batch 2016, 2017, 2018. Data collection techniques using questionnaires. The instrument quality testing techniques include validity test and reliability test. The analysis used is descriptive analysis and classical assumption test such as normality test, multicolinearity test and heterosesticity test. The data analysis technique used in this study is multiple linear regression tests. The results showed that: (1) Motivation variables partially positively and significantly affect Academic Achievement, (2) Discipline variables negatively and significantly affect Academic Achievement, (3) Self Confidence variables partially positively and significantly affect Academic Achievement, (4) Motivation, Discipline and Self Confidence simultaneously or together have a positive and significant influence on Academic Achievement.